The Effect of Definitions toward Students’ Vocabulary - Tawali Tawali (Universitas Pendidikan Mandalika, 2018)
This research is aimed to find out the effect of definitions toward students’ vocabulary mastery: it was an experimental study at the second grade student of MTs NW Haqqul Yaqin Sayang- sayang. The subject of this research was the second grade of MTs NW Haqqul Yaqin Sayang- sayang.The research was used experimental method with quantitative approach. The population of this research consist of 55 students, and the sample is 29 for experimental group while 26 for control group. The technique of collecting data was used definition for experimental group and matching word with antonym for control group. The data was collected by using post-test only and the data was analyzed by t-test formula. Based on data analysis the mean score of experimental group was 76,4 and control group was 69,23, beside of that standard deviation for experimental group was 114,28 and for control group was 113,09 and the value of t-test was 2,44 and t-table was 2,000. Degree of freedom is 53 with significant level 0,05. It means that the value of t-test was higher than t-table (t-test ˃ t-table). The alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Thus, the conclusion of this research was there was an effect of definition toward students’ vocabulary mastery: an experimental study at the second grade students of MTs NW Haqqul Yaqin Sayang-sayang.